2015
DOI: 10.13005/bpj/618
|View full text |Cite
|
Sign up to set email alerts
|

Bioimprinting Based Scaffold Development for Tissue Engineering Applications

Abstract: In this article we report the development of scaffold mimicking the cell surface topography. Using Soft lithography, in which polymer (triglyme, ethylene glycol dimethacrylate, methacrylic acid and IRGAcure 2022) is applied over the cultured cell and cured instantly using UV source. IRGA cure 2022 is a photoinitiator, which helps in solidification of the polymer when exposed to UV light source. Triglyme helps to increase the viscosity of the polymer. This method can be applied to all adherent cells. This scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…69 The study proceeded to characterise the ideal properties of scaffold used in implants, and demonstrates the promise of such bioimprinting approach on cell growth. 74 Tan et al also report the imprinting of Ishikawa endometrial cancer cells, in this case using polymethacrylate (pMA) and polystyrene (pST). 71 The studies compared a culture of cells on each bioimprint type and compared them to those on flat (non-imprinted) substrates.…”
Section: Cell Culture Platformsmentioning
confidence: 97%
See 1 more Smart Citation
“…69 The study proceeded to characterise the ideal properties of scaffold used in implants, and demonstrates the promise of such bioimprinting approach on cell growth. 74 Tan et al also report the imprinting of Ishikawa endometrial cancer cells, in this case using polymethacrylate (pMA) and polystyrene (pST). 71 The studies compared a culture of cells on each bioimprint type and compared them to those on flat (non-imprinted) substrates.…”
Section: Cell Culture Platformsmentioning
confidence: 97%
“…68 Vigneswaran et al proposed bioimprinted substrates to be scaffolds for the development of tissue engineering technology. 69,74 The studies both imprinted Ishikawa endometrial cancer cells into a UV fast-cure polymer. The results replicated studies showing the topology of the bioimprint to be representative of template cells on a micro and nanoscale.…”
Section: Cell Culture Platformsmentioning
confidence: 99%
“…From table 1, it can 8 Tetraethoxysilane Sol-gel [46,74] also be concluded that the investigation based on nanoparticle composite for cell imprint replica fabrication process has not been reported. As far as applications like cell guiding [31,48], cell adhesion [49,50], regenerative medicine [51,52], cell or tissue microenvironments [53][54][55], implants [56], bone-tissue engineering [18], tissue engineering [57][58][59][60], cell fate [16,34,61], drug delivery [54] and smart culture substrates [60,[62][63][64] are concerned, property tailoring of the biomimetic bioreplicated materials is highly demanding. Thus, doping of nanoparticles can help to modify the physical, chemical, mechanical and electrical properties of the fabricated composites for bio-replicated biomimetic applications.…”
Section: Cell Replication and Techniquesmentioning
confidence: 99%